POTENSI LARVA LALAT TENTARA HITAM RENDAH LEMAK TERHADAP KECERNAAN DAN FERMENTASI RUMEN IN VITRO SEBAGAI BAHAN PAKAN ALTERNATIF - Mulianda, Randi; Dewi, Rita Roswita; Rusdhi, Alfath; Kejora, Emmy; Martha, Reno; Harahap, Ari Ashari (Fakultas Pertanian Universitas Garut, 2025)
Purpose: This study aimed to evaluate the differences in nutritional value between whole BSF larvae and defatted BSF larvae through chemical analysis and in vitro rumen fermentation trials. Methods: Four treatments were tested: whole BSF larvae (T1), mechanically defatted BSF larvae (T2), chemically defatted BSF larvae (T3), and soybean meal as a control (T4). Proximate analysis and Van Soest fiber fraction methods were performed. Results: Defatting improved dry matter and organic matter digestibility as well as gas production compared with whole BSF larvae. Ammonia concentration and VFA showed no significant differences among treatments. Conclusion: Fat reduction in BSF larvae enhanced their quality in in vitro rumen fermentation, indicating their potential as an alternative feed ingredient for ruminant livestock.